PENGARUH PENERAPAN PROGRAM MENTORING AL-ISLAM TERHADAP PRAKTIK BERAGAMA MAHASISWA UNIVERSITAS ISLAM OGAN KOMERING ILIR KAYUAGUNG - Firmansyah Firmansyah (PAI RAFAH, 2020)
This research was conducted to determine the effectiveness of the implementation of the mentoring Al-Islam program at Universitas Islam OganKomeringIlir (UNISKI) Kayuagung which has been running so far, the implementation of the religious practice of students of UNISKI Kayuagung, and what effect the implementation of the mentoring Al-Islam program has on the implementation of the student's religious practice. This research is a descriptive field research with a quantitative approach. The data sources were students participating in the mentoring Al-Islam and the management of P5I UNISKI Kayuagung. Data collection is done using observation techniques, questionnaires, interviews, and documentation. The data analysis is done through descriptive statistical techniques. The results of the data analysis showed that the effectiveness of the implementation of the mentoring Al-Islam program at UNISKI Kayuagung based on the response data of 284 respondents to the research questionnaire using the one-sample t-test formula = 173,433> price of the table, both at the error level ( ) 5% = 1,645 or 1% = 2,362. Thus, the Ha submitted can be accepted. Meanwhile, the value of students' religious practice, using the t-test formula of one sample, the price of t arithmetic = 156.8> t table 5% = 1.645 and 1% = 2.362. The price of t arithmetic falls on the acceptance of Ha, so Ha is accepted and H0 is rejected. The statistical calculation using the product moment correlation formula shows that the application of the mentoring Al-Islam program has a positive and significant effect of 0.996 with a "very strong" relationship level on the religious practice of students of UNISKI Kayuagung.